Variations in green investment efficiency of enterprises under different low-carbon emission reduction strategies - Ping Wu (Energy Informatics)
Abstract As environmental issues become more prominent, enterprises increasingly focus on reducing low-carbon emissions through green investment. Simultaneously, governments have implemented various low-carbon emission reduction strategies. This study assesses how varying low-carbon emission reduction strategies influence green investment efficiency in enterprises. The study employed the widely used a slack-based model (SBM) in efficiency estimation to analyze the variations in green investment efficiency under command-based, incentive-based, and public-based strategies. The findings revealed that the coefficient for the command-based strategy was − 0.456, the coefficient for the incentive-based strategy was 0.555, and the coefficient for the public-based strategy was 0.133. All coefficients were statistically significant at the 1% level. The regression analysis results aligned with hypotheses H1-H3, indicating that the command-based strategy hampered green investment efficiency while the incentive-based and public-based strategies enhanced it. These results demonstrate that diverse low-carbon emission reduction strategies yield varying impacts on enterprises’ green investment efficiency. The research results can provide a basis for policy-making in the actual government environmental protection departments.